2013
DOI: 10.1016/s0924-9338(13)77069-x
|View full text |Cite
|
Sign up to set email alerts
|

2196 – The association between body image issues and women's sexual functioning through the lens of the objectification theory

Abstract: IntroductionPhysical appearance is a major component of human sexuality. Body image is associated with females' sexual functioning; and poor body image is strongly related to sexual functioning problems (SFP). SFP are becoming more pervasive throughout Western culture. Objectification Theory (OT) provides a framework for understanding how sociocultural pressure is translated into psychological risk factors that promote body concerns and SFP. Previous research indicated that the core constructs of OT (body moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Issues with self-esteem, self-worth, and isolation or withdrawal are common symptoms of depression; the prevalence of these issues in participants' stories is unsurprising. Feelings of ostracization resulting from gendered racism can affect perceptions of worth and body image, both of which were disclosed by participants (Dakanalis & Riva, 2013;Watson et al, 2019). Lastly, consistent with emerging empirical evidence on gendered racism and anxiety, participants noted the presence of anxiety as a psychological consequence (Wright & Lewis, 2020).…”
Section: Psychological Consequencessupporting
confidence: 67%
See 1 more Smart Citation
“…Issues with self-esteem, self-worth, and isolation or withdrawal are common symptoms of depression; the prevalence of these issues in participants' stories is unsurprising. Feelings of ostracization resulting from gendered racism can affect perceptions of worth and body image, both of which were disclosed by participants (Dakanalis & Riva, 2013;Watson et al, 2019). Lastly, consistent with emerging empirical evidence on gendered racism and anxiety, participants noted the presence of anxiety as a psychological consequence (Wright & Lewis, 2020).…”
Section: Psychological Consequencessupporting
confidence: 67%
“…Past research demonstrates a linkage between gendered racism and depression (Carr et al, 2014), suicidality (Carr et al, 2013), anxiety (Wright & Lewis, 2020), alcohol-related consequences (Davis et al, 2014), and traumarelated symptoms . As another manifestation of gendered racism, factors like internalization of racialized stereotypes and Eurocentric beauty ideals contribute to body shame, disordered eating, and excessive weight management among Black women (Dakanalis & Riva, 2013;Gentles-Peart, 2018;Watson et al, 2019).…”
Section: Racism Sexism and Black Women's Mental Healthmentioning
confidence: 99%
“…Objectification theory has been researched in lesbian women, with similar levels of reported self-objectification found between lesbian and heterosexual women (Hill & Fischer, 2008). There is a strong link between cultural sexual objectification, objectifying messages and themes from mainstream media, and the negative body image-related psychological outcomes of self-objectification (Dakanalis & Riva, 2013). Moradi (2010) further reported that Stice's sociocultural model of body image overlaps with objectification theory because internalization is a key component of both theories.…”
Section: Discussionmentioning
confidence: 91%
“…Self-objectification manifests through the practice of body monitoring, that is, using cognitive resources for evaluation of one's body appearance from an observer's perspective to determine whether one's body is attractive enough and hence, good enough (Calogero, 2012;Mckinley & Hyde, 1996). Even though objectification theory was developed as an attempt to explain the effects of self-objectification in women, such as body shame and sexual dysfunction (Dakanalis & Riva, 2013), more recent research demonstrates the prevalence of self-objectification in men (Frederick et al, 2022;Harsey & Zurbriggen, 2021).…”
Section: Self-objectificationmentioning
confidence: 99%